2015
DOI: 10.1093/jrr/rrv025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indirect actions and oxygen on relative biological effectiveness: estimate of DSB induction and conversion induced by gamma rays and helium ions

Abstract: Clustered DNA damage other than double-strand breaks (DSBs) can be detrimental to cells and can lead to mutagenesis or cell death. In addition to DSBs induced by ionizing radiation, misrepair of non-DSB clustered damage contributes extra DSBs converted from DNA misrepair via pathways for base excision repair and nucleotide excision repair. This study aimed to quantify the relative biological effectiveness (RBE) when DSB induction and conversion from non-DSB clustered damage misrepair were used as biological en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 63 publications
(74 reference statements)
2
9
0
Order By: Relevance
“…This study evaluated the DSB induction and repair outcomes in the presence of DMSO and/or under hypoxia. The MCDS-derived results for DSB induction for low- and high-LET radiations have been compared with experimental data and track structure simulations elsewhere [ 38 , 39 , 40 , 45 , 47 , 48 ], including the data for the presence of DMSO or under hypoxia [ 24 , 25 ]. Recent experimental data showed that the yields for DSB induction in WiDr (human colon carcinoma) cells irradiated with 6 MV X-rays in the presence of 0.28 M DMSO decreased to 62% using pulse-field gel electrophoresis assay [ 22 ] while MCDS simulation showed that the DSB yields reduced to 54%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study evaluated the DSB induction and repair outcomes in the presence of DMSO and/or under hypoxia. The MCDS-derived results for DSB induction for low- and high-LET radiations have been compared with experimental data and track structure simulations elsewhere [ 38 , 39 , 40 , 45 , 47 , 48 ], including the data for the presence of DMSO or under hypoxia [ 24 , 25 ]. Recent experimental data showed that the yields for DSB induction in WiDr (human colon carcinoma) cells irradiated with 6 MV X-rays in the presence of 0.28 M DMSO decreased to 62% using pulse-field gel electrophoresis assay [ 22 ] while MCDS simulation showed that the DSB yields reduced to 54%.…”
Section: Discussionmentioning
confidence: 99%
“…In RT, the use of dimethylsulfoxide (DMSO) as a ROS scavenger reduces the yields of DSB induction for both low and high-LET radiations [ 21 ] and increases cell survival [ 22 , 23 ]. Monte Carlo simulations and experiments also demonstrated that DMSO reduces the mutation frequency and increases the probability of correct repair [ 24 , 25 ]. Besides, DMSO can be used in RT to reduce the side effects [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…LET is a measure of ionization density and it is defined as the average energy (keV) transferred by a particle along the 1 μm path [ 89 ]. High LET particles show high ionization density, thus inducing increased direct cell damage, but display lower indirect effects mediated by ROS and other radicals [ 89 , 90 ]. Another main advantage of particle-based radiation therapy is the finite dose deposition in the tissue that allows sparing the normal brain tissue.…”
Section: New Frontiers To Improve Radiotherapy: Evaluating the Potmentioning
confidence: 99%
“…LET is a measure of ionization density and it is defined as the average energy (keV) transferred by a particle along the 1 µm path [89]. High LET particles show high ionization density, thus inducing increased direct cell damage, but display lower indirect effects mediated by ROS and other radicals [89,90]. Another main advantage of particle-based radiation therapy is the finite dose deposition in the tissue that allows sparing the normal brain tissue.…”
Section: New Frontiers To Improve Radiotherapy: Evaluating the Potential Of Synergistic Approachesmentioning
confidence: 99%